Pengaruh Penggunaan Learning Management System (LMS) Dan Motivasi Terhadap Kompetensi Mahasiswa PPG Universitas Negeri Jakarta Tahun 2021 - Sri Nur Aini; Siti Nurjanah; Aditya Pratama (Peneliti.net, 2023)
This study aims to determine the direct effect of using LMS and Motivation of PPG Student Competence. The method used is a quantitative survey approach. With a sample of 320 who are PPG Students in Position at UNJ in 2021. The data used is in the form of primary and secondary data. Secondary data was obtained from LPTK UNJ in the form of UKIN scores for student competency. Meanwhile, primary data was obtained using closed and open questionnaires. The data analysis used in this study is Path Analysis with the help of SPSS version 25. The results of the first hypothesis research show that the use of LMS has a positive direct effect on student competence with a magnitude of 0.325. In the second hypothesis, motivation has a direct positive effect on the competency of PPG students with a magnitude of 0.313. Furthermore, the third hypothesis is accepted, which means the use of LMS has a direct positive effect on motivation with a magnitude of 0.706. And the fourth hypothesis is accepted, meaning that there is an indirect effect of using LMS on student competency through motivation of 0.221 with a p-value <0.05 which means motivation has a role in mediating LMS use on student competence. So that it can be said that motivation has a dual role in influencing student competence directly and indirectly.